Somewhat Opinionated An America dance journal - Barnes, Clive 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Joyce Theater, New York City 4 April. New York City Center 23 April. New York State Theater 25 April-25 June. Rose Theater, Lincoln Center 26 April. Performing Arts Center, Purchase, NY 30 April. House Gilman Opera House, Brooklyn Academy of Music 3 May. Joyce Theater 6-7 May. Joyce Theater 9 May. Metropolitan Opera House 22 May-30 June. Joyce Theater 31 May. Capitol Theater Salt Lake City, Utah 1 June. Peter Jay Sharp Theater, Juilliard 5 June. Kennedy Center Washington, DC 20-25 June. PALABRAS CLAVE: James Sewell ballet, annual Youth America Grand Prix, Diamond Project, New York City Ballet, Akram Khan, Edward Villella's Miami City Ballet, Krammer / Krammer, Eliot Feld's Ballet Tech, Jonas Kage's Ballet West, Annual Workshop of the School American Ballet, Wheeldon's "Garland Dance".